Integrating a Statewide HIV Call Line: An Innovative and Tailored Approach for Rapid Linkage to HIV Care. (November 2017) - Coleman, Tyffany Evans; LeViere, Anna; Carcano, Joaquin; Bailey, Michelle; Heine, Amy; Quinlivan, Evelyn Byrd; Gay, Cynthia
Abstract : N/A: Only 80% of people living with HIV (PLWH) in the United States are linked to care, 40% are engaged in care, and 30% have achieved viral load suppression. We addressed linkage to care with a pilot program of a statewide referral call center to connect PLWH and their non‐HIV specialty providers to HIV care. Callers received tailored referrals from nurses trained to work in an existing call center, using an electronic assessment tool and a comprehensive HIV provider list. Of 122 calls, 85% were from PLWH and 15% from providers calling about a patient. Overall, 88 of 104 (84.6%) PLWH and 16 of 18 (88.9%) providers accepted care referral, including 13% of PLWH callers without prior HIV care. Results indicated that the call center was an acceptable strategy for HIV care referral; the use of an existing call center facilitated feasibility of the program and improved linkage to HIV care.